2011
DOI: 10.1177/0885728811399090
|View full text |Cite
|
Sign up to set email alerts
|

Students With Intellectual Disabilities

Abstract: This study examined the outcomes of 409 students with mental retardation or multiple disabilities from 177 school districts in a Great Lakes state. These students with intellectual disabilities were interviewed at exit and 1 year following graduation. The authors developed and tested three regression models-two to predict full-time employment and one to predict college enrollment after graduation. Although inclusion was a significant predictor of postsecondary education, career and technical education and work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 10 publications
(27 reference statements)
4
37
0
Order By: Relevance
“…Their impact on outcomes is only an indirect one which happens through adaptive behavior and parent expectations. This finding extends previous literature regarding these demographic factors which has suggested that they predict outcomes (Baer et al, 2011;Fleming & Fairweather, 2012;Sima et al, 2015), although none of those studies included measures of adaptive behavior or parent expectations. Our findings suggest that, rather than directly affecting outcomes, these demographic factors are one step in a more complex process along a pathway that determines outcomes for youth with ID, and that the direct relationship from demographic factors to outcomes disappears with the addition of adaptive behavior and parent expectations.…”
Section: Department Ofsupporting
confidence: 83%
“…Their impact on outcomes is only an indirect one which happens through adaptive behavior and parent expectations. This finding extends previous literature regarding these demographic factors which has suggested that they predict outcomes (Baer et al, 2011;Fleming & Fairweather, 2012;Sima et al, 2015), although none of those studies included measures of adaptive behavior or parent expectations. Our findings suggest that, rather than directly affecting outcomes, these demographic factors are one step in a more complex process along a pathway that determines outcomes for youth with ID, and that the direct relationship from demographic factors to outcomes disappears with the addition of adaptive behavior and parent expectations.…”
Section: Department Ofsupporting
confidence: 83%
“…Education, however, does not affect the chances of being employed among persons with intellectual disability. This is confirmed by the finding of Baer et al (2011). Although, emotionally disabled persons have higher employment probability, they do not have the highest educational attainment among the types of PWDs.…”
Section: Logit Regression For Determinant Of Employment In Ghanasupporting
confidence: 53%
“…Of the 22 studies, 11 were exploratory, seven were a priori, and four were a priori with PSA. Of the 22 studies, one examined data from the Educational Longitudinal Study of 2002(i.e., Rojewski et al, 2014, five studies examined data from state-level databases (i.e., Daviso et al, 2016;Flexer et al, 2011;Rabren et al, 2014;Simonsen & Neubert, 2013), and 16 studies examined data from the NLTS2 database (e.g., Cmar, 2015;Connors et al, 2014;Petcu et al, 2017;Shogren et al, 2017). The current review included no additional evidence for six predictors (i.e., career awareness, community experiences, interagency collaboration, occupational courses, parent involvement, travel skills) and additional evidence for 14 predictors.…”
Section: Resultsmentioning
confidence: 97%
“…Of the remaining 34 studies, two (i.e., Flexer et al, 2011) were included in Haber et al (2016). These two studies were included as part of this review because they had not been reviewed for quality or included as part of the predictor research base identified by or Mazzotti et al (2016).…”
Section: Selection Procedures Inclusion/exclusion Criteriamentioning
confidence: 99%